(untitled) (Revista de Ciências Agroveterinárias, 2021)
This study aimed to evaluate the contamination by Salmonella sp. in the Capinzal River, to determine the prevalent serovars, patterns of antimicrobial resistance, and the genetic relationships between the serovars identified. A total of 108 samples were collected from 2016 to 2018. The isolation of Salmonella spp. was conducted according to International Organization for Standardization (ISO) standards. The antimicrobial resistance profile of the Salmonella isolates was evaluated, and isolates were selected for serotyping and verification of genetic similarity using the Pulsed-Field Gel Electrophoresis (PFGE) Technique. Of the 108 samples collected, 35 (32.4%) were positive for Salmonella; 17.2% of the isolates were from the rural area; and 88.6% were from the urban area. Salmonella was isolated from all collect points along the river, with a higher incidence at the beginning of the urban area, indicating that contamination starts in the rural area and intensifies in the urban area of the city. A percentage of 35.1% of the Salmonella isolates were resistant to at least two antibiotics, while 18.9% were considered multidrug-resistant (resistant to at least two antibiotics of different classes). Seven serovars were distinguished from the serotyped isolates, with a prevalence rate of 23.5% for S. Infantis, S. Orion, and S. Javiana; 11.8% for S. Senfterberg, and 5.9% for S. Montevideo, S. Heidelberg, and S. enterica subsp. enterica (O: 6.8). The variability in specific restriction sites generated by PFGE resulted in 10 pulsotypes, separating mainly different serotypes.